The influence of tourism product on tourist decision to visit Anyer - Ika Utami Widyaningsih; Mulyanah Mulyanah (Universitas Negeri Padang, 2022)
Anyer is the one of the famous beach tourism destinations on the western of Java Island. This research aims to obtain the empirical evidence about the influence of tourism product to decision to visit on Novus Jiva Anyer. This study used quantitative research that distributed data by questionnaires. Sample in this research were the tourist of Novus Jiva Anyer, and the sampling technique used is simple random sampling with a total sample of 173 respondens. Empirical evidence show that the visitors are mostly from outside Banten province. Where they get an information about tourism product from social media such as websites, instagram, whatsapp, and tourist booking application (traveloka, booking.com, etc). The results prove that trourism products have a positive and significant affect to tourist visiting decisions. From the result, this research can be useful as knowledge and consideration for tourist attractions manager in improving quality to attract tourist visitors.